A pocket history of human evolution : how we became sapiens - Condemi, Silvana; Savatier, François, 1961- (The Experiment, 2019)
"A concise, illustrated update on our earliest ancestors (Homo erectus, ergaster, the Neanderthals, Denisovans, and other) and what accelerated Homo sapiens' evolution and left us the sole surviving species among many other ancient bipedal "humans""--